Granulocyte-macrophage colony-stimulating factor is not involved in production of reactive nitrogen intermediates by or toxoplasmastatic activity of gamma interferon-activated murine macrophages. - Buisman, A (1994)
The induction of reactive nitrogen intermediates (RNI) and toxoplasmastatic activity of murine macrophages by recombinant gamma interferon (rIFN-gamma) is mediated by an autocrine pathway involving tumor necrosis factor alpha (TNF-alpha). To investigate whether cytokines other than TNF-alpha play a role in the activation of these effector functions, granulocyte-macrophage colony-stimulating factor (GM-CSF) was studied. Recombinant GM-CSF (rGM-CSF) could stimulate peritoneal macrophages, since this cytokine stimulated the production of prostaglandin E2 by these cells. However, rGM-CSF did not induce either the release of RNI by or the toxoplasmastatic activity of macrophages. rGM-CSF in combination with various concentrations of rIFN-gamma did not enhance these effector functions more than rIFN-gamma alone. Furthermore, neutralization of endogenously produced GM-CSF by monoclonal antibodies did not affect the release of RNI by or the toxoplasmastatic activity of rIFN-gamma-activated macrophages. Together these results indicate that GM-CSF is not involved in RNI production by and toxoplasmastatic activity of IFN-gamma-activated murine macrophages.